2021
DOI: 10.1002/tpg2.20177
|View full text |Cite
|
Sign up to set email alerts
|

Pangenomics in crop improvement—from coding structural variations to finding regulatory variants with pangenome graphs

Abstract: Since the first reported crop pangenome in 2014, advances in high‐throughput and cost‐effective DNA sequencing technologies facilitated multiple such studies including the pangenomes of oilseed rape (Brassica napus L.), soybean [Glycine max (L.) Merr.], rice (Oryza sativa L.), wheat (Triticum aestivum L.), and barley (Hordeum vulgare L.). Compared with single‐reference genomes, pangenomes provide a more accurate representation of the genetic variation present in a species. By combining the genomic data of mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

7
2

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 156 publications
(181 reference statements)
0
32
0
Order By: Relevance
“…However, studies of PAV normally present genomic variation among genetically divergent accessions of a species population rather than somatic and meiotic mutations within single genotypes. Moreover, PAV analyses generally focus on the concept of core and disposable genes, which despite the value for pangenomic studies does not illustrate the potential regulatory role of non-coding genomic regions (Zanini et al, 2022). In this study, spontaneous exchanges and segmental deletions covering both coding and non-coding regions were shown to contribute to unexpected genetic diversity within F1 offspring from two homozygous parents.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies of PAV normally present genomic variation among genetically divergent accessions of a species population rather than somatic and meiotic mutations within single genotypes. Moreover, PAV analyses generally focus on the concept of core and disposable genes, which despite the value for pangenomic studies does not illustrate the potential regulatory role of non-coding genomic regions (Zanini et al, 2022). In this study, spontaneous exchanges and segmental deletions covering both coding and non-coding regions were shown to contribute to unexpected genetic diversity within F1 offspring from two homozygous parents.…”
Section: Discussionmentioning
confidence: 99%
“…Another type of pangenome graph is the practical haplotype graph (PHG) [ 92 , 93 ], which is a trellis graph representing genic and intergenic regions. PHGs avoid challenges in aligning repetitive and highly divergent regions through the use of a reference genome coordinate system that uses genes to anchor sequences [ 92 , 94 ], minimising errors due to reference bias, poor alignment and miscalled variants [ 95 ].…”
Section: Developments In Pangenome Resources To Aid In the Breeding O...mentioning
confidence: 99%
“…Plant pangenome assemblies have shown that variable regions are often associated with biotic or abiotic stress [ 93 ], leading researchers to focus on the construction of pangenomes based on specific functional traits. These trait pangenomes aim to describe the landscape of genetic variation related to a trait.…”
Section: Developments In Pangenome Resources To Aid In the Breeding O...mentioning
confidence: 99%
“…Copy number variations (CNVs) and presence/absence variations (PAVs) occur due to these genomic polymorphisms (Alkan et al, 2011; Sedlazeck et al, 2018a). Insertions and deletions can have a strong effect on crop traits and have been shown to play a role in domestication and environmental adaptation (Gill et al, 2021; Tao et al, 2019; Yildiz et al, 2022; Zanini et al, 2022; Żmieńko et al, 2014). Until recently, the lack of high-quality reference assemblies and the complex nature of often large, polyploid genomes made comprehensive SVs exploration challenging in crop genomic research (Meyers and Levin, 2006; Yuan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%